Production and functionality of quinoa (Chenopodium quinoa) protein concentrate - Scanlin, Laurie Ann, author; Stone, Martha B., advisor; Lorenz, Klaus J., committee member; Sampson, David A., committee member; Ward, Sarah M., committee member (Colorado State University. Libraries, 2006)
Four whole grain quinoa [two commercial genotypes from Colorado (black and white) and two abrasion conditions (polished and unpolished)] were analyzed for saponin, ash, fat, moisture, nitrogen, 1000-grain weight, and yield loss. Whole grain materials were defatted under controlled conditions and analyzed for nitrogen content. Quinoa protein concentrate was prepared from defatted flour by a modified isoelectric precipitation method and analyzed for nitrogen content and nitrogen recovery. Quinoa protein was characterized by amino acid analyses, chemical score, SDS-PAGE, and isoelectric focusing. Wheat pasta was fortified with quinoa protein concentrate at two levels, 3.5% or 7.0% and effects of formulation modification and cooking times on cooking characteristics were evaluated. Effects of formulation modification on color of dry pastas and sensory characteristics of cooked pastas were also evaluated. A consumer sensory panel rated pasta treatments for sensory characteristics using 9-point hedonic scales. When black and white quinoa genotypes were polished saponin was reduced, but the magnitude of the reduction was less in black quinoa compared to white quinoa. An 11% loss in fat was found in the white quinoa after polishing. Nitrogen increased after polishing, but the magnitude was greater in white quinoa compared to the black quinoa. Yield loss due to polishing was 13% in black and white quinoa. Defatted quinoa was 2.3% lower in nitrogen content than whole quinoa. Nitrogen content of quinoa protein concentrates increased with polishing, but the magnitude was higher in the white quinoa than the black quinoa. Nitrogen recoveries were highest in white quinoa. Mean nitrogen values for quinoa protein concentrate ranged from 11.23 to 14.83% (dwb). Amino acid analyses were comparable to reported values for quinoa. Quinoa protein concentrate received a chemical score of 91. Major quinoa proteins with molecular weights of approximately 11 and 30 kDa and isoelectric points of 4.4, 5.4, 5.6, and 5.8 were identified. Differences in cooking characteristics and color of dry pastas were found among pasta treatments. Lysine content was increased by 40% or 80% by formulation modification of semolina pasta with quinoa protein concentrate at levels of 3.5% or 7.0%, respectively, without affecting sensory characteristics.